2010
DOI: 10.1038/nature09018
|View full text |Cite
|
Sign up to set email alerts
|

Affinity gradients drive copper to cellular destinations

Abstract: Copper is an essential trace element for eukaryotes and most prokaryotes. However, intracellular free copper must be strictly limited because of its toxic side effects. Complex systems for copper trafficking evolved to satisfy cellular requirements while minimizing toxicity. The factors driving the copper transfer between protein partners along cellular copper routes are, however, not fully rationalized. Until now, inconsistent, scattered and incomparable data on the copper-binding affinities of copper protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
434
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 425 publications
(454 citation statements)
references
References 36 publications
19
434
1
Order By: Relevance
“…At a higher Bcs concentration (Ͼ200 M) where Atox1-type proteins compete strongly for Cu I , GSH cannot compete (even at millimolar concentration; supplemental Tables S3 and S4). This result contrasts with that from gas phase experiments that concluded that the affinity of GSH for Cu I is similar to that of Dtt and that it can compete for Cu I with the Atox1 protein (16). The current uncertainties associated with ESI-MS detection are addressed under the "Discussion.…”
Section: Resultscontrasting
confidence: 54%
See 3 more Smart Citations
“…At a higher Bcs concentration (Ͼ200 M) where Atox1-type proteins compete strongly for Cu I , GSH cannot compete (even at millimolar concentration; supplemental Tables S3 and S4). This result contrasts with that from gas phase experiments that concluded that the affinity of GSH for Cu I is similar to that of Dtt and that it can compete for Cu I with the Atox1 protein (16). The current uncertainties associated with ESI-MS detection are addressed under the "Discussion.…”
Section: Resultscontrasting
confidence: 54%
“…The absolute dissociation constant log K D ϭ Ϫ15.3 for the 1:1 complex was estimated via potentiometric titration of Cu I -Dtt samples prepared in situ via Dtt reduction of Cu 2ϩ (39). As Dtt has been used previously as both a competing ligand and an affinity standard for estimation of the Cu I affinities of proteins (16,40), its Cu I binding stoichiometry and affinity were re-investigated here to provide a unified scale.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, these features make free copper ions toxic by outcompeting other metal ions in binding the target metalloproteins and as a source of reactive oxygen species (1). Living organisms thus resort to different strategies aimed to transport copper ions and regulate their levels in the cell, such as the use of metallochaperones, which bind copper ions and deliver them specifically to the target proteins (2)(3)(4)(5)(6).…”
Section: Sco Proteinsmentioning
confidence: 99%